Al Source-Drain Schottky contact enabling N-type (Back Enhanced) BESOI MOSFET - Carvalho, Henrique L.; Rangel, Ricardo C.; Sasaki, Katia R. A. [UNESP]; Agopian, Paula G. D. [UNESP]; Yojo, Leonardo S.; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work presents for the first time the experimental and simulated characteristics of a BESOI MOSFET reconfigurable transistor with non-sintered aluminum contact. Without this sintering process, the transistor acquires a higher current for electrons, but doesn't have significant current for holes. This characteristic is opposite to those previously observed in sintered transistors. The thermal process of sintering caused interference in the formation of the Schottky junction, this result can be used to improve future implementations of the BESOI MOSFET.
Keywords: BESOI MOSFET; aluminum; reconfigurable device; Schottky contact; source and drain contacts